Gas diffusion layer, preparation method thereof and proton exchange membrane fuel cell applying gas diffusion layer

Through spraying technology, the conductive powder slurry is mixed with the hydrophobic slurry and sprayed on the hydrophobic carbon paper while stirring, which solves the problem of uneven dispersion of conductive powder in the slurry, improves the uniformity of the microporous layer and the performance of the fuel cell, and achieves efficient preparation of the gas diffusion layer.

CN119601679APending Publication Date: 2025-03-11SHAANXI MEILAND NEW MATERIALS CO LTD +1

Patent Information

Application Number
CN202411831506.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When the existing wet coating method prepares the microporous layer, the conductive powder is unevenly dispersed in the slurry, resulting in settlement during the coating process, affecting the uniformity of the microporous layer and the performance of the fuel cell.

Method used

The microporous layer is prepared by spraying technology. By mixing the hydrophobic agent with water to form a hydrophobic slurry A, mixed with conductive powder slurry B composed of conductive powder, surfactant and binder, etc., to form spray slurry C, and spray on the hydrophobic carbon paper during the stirring process to ensure the dispersion and uniformity of the conductive powder.

Benefits of technology

The dispersion uniformity and surface roughness of the microporous layer are improved, the limit current density and current stability of the gas diffusion layer are increased, and the power density is up to 1.4W/cm-2, while improving product batch stability and saving slurry usage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601679A_ABST
    Figure CN119601679A_ABST
Patent Text Reader

Abstract

The invention relates to the field of fuel cells, and particularly discloses a gas diffusion layer, a preparation method thereof and a proton exchange membrane fuel cell applying the gas diffusion layer, and the preparation method of the gas diffusion layer comprises the following steps: preparing porous substrate layer carbon paper; performing hydrophobic treatment on the porous substrate layer carbon paper to obtain hydrophobic carbon paper; a hydrophobic agent and water are mixed to obtain hydrophobic slurry A, conductive powder, a surfactant, a binder and an organic solvent are mixed and dispersed to obtain conductive powder slurry B, the hydrophobic slurry A and the conductive powder slurry B are mixed to form spraying slurry C, the spraying slurry C is sprayed on hydrophobic carbon paper while being stirred, drying and curing are conducted after spraying, and a microporous layer is formed. A gas diffusion layer is obtained; the invention further discloses the gas diffusion layer prepared by adopting the method and the proton exchange membrane fuel cell applying the gas diffusion layer. The application has the characteristics of solving the problems of dispersion uniformity of the conductive powder in the slurry and sedimentation in the coating process, improving the quality of the microporous layer and further improving the performance of the fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel cells, and more specifically, to a gas diffusion layer and a preparation method thereof and a proton exchange membrane fuel cell using the same. Background Art

[0002] Proton exchange membrane fuel cells (PEMFC) have become the main application direction of hydrogen energy at the battery end due to their pollution-free, high energy conversion rate, simple design, fast reaction kinetics, and low start-up temperature. The gas diffusion layer (GDL) is one of the core components of the PEMFC membrane electrode. In PEMFC, it supports the catalyst layer, collects current, and provides a path for the reaction gas and product water. It has excellent mechanical properties, conductivity, pore structure, and uniformity.

[0003] GDL is usually composed of a porous substrate layer (MPS) with large pores and a microporous layer (MPL) with small pores. Carbon fiber paper (abbreviated as carbon paper) is the preferred material for MPS; MPL is usually a mixture of conductive powder and hydrophobic agent. The main function of MPL is to manage the generated water, control the distribution and transmission of water, prevent the flooding effect, maintain the wet state of the electrolyte membrane, improve the interface between the catalyst layer and the carbon paper layer, and improve the durability of the gas diffusion layer. It is crucial for the normal operation of the battery.

[0004] The MPL layer is usually prepared by uniformly applying a mixture of conductive powder and hydrophobic agent on the surface of MPS by coating, spraying or screen printing, and then curing at high temperature to obtain MPL. At present, the preparation process of the microporous layer mainly involves mixing conductive carbon powder, dispersant and hydrophobic agent into slurry by solvent, applying it to the surface of carbon paper by wet method, and drying to form a microporous layer. For example, CN114464834A and CN114927704A both use coating method to prepare microporous layer, apply carbon slurry on one side of hydrophobic carbon fiber paper, and obtain gas diffusion layer by drying and sintering.

[0005] However, the current wet coating method has the following problems: the conductive powder is difficult to disperse in the solvent. After adding a dispersant and dispersing it through stirring, ultrasound and other means, sedimentation will occur during the coating process, resulting in poor uniformity of the coated microporous layer, which in turn increases the surface roughness of the GDL and affects the performance of the fuel cell. Therefore, solving the problems of uniformity of dispersion of the conductive powder in the slurry and sedimentation during coating is of great significance to improving the quality of the microporous layer and thus improving the performance of the fuel cell. Summary of the invention

[0006] In order to solve the problem of uniform dispersion of conductive powder in slurry and sedimentation during coating, improve the quality of microporous layer and thus improve the performance of fuel cell, the present application provides a gas diffusion layer and a preparation method thereof and a proton exchange membrane fuel cell using the same.

[0007] In a first aspect, the present application provides a method for preparing a gas diffusion layer, using the following technical solution: A method for preparing a gas diffusion layer comprises the following steps: S1, preparing a porous base layer of carbon paper; S2, performing hydrophobic treatment on the porous substrate carbon paper to obtain hydrophobic carbon paper; S3, mixing a hydrophobic agent with water to obtain a hydrophobic slurry A, mixing and dispersing a conductive powder, a surfactant, a binder and an organic solvent to obtain a conductive powder slurry B, mixing the hydrophobic slurry A with the conductive powder slurry B to form a spray slurry C, and then spraying the spray slurry C on a hydrophobic carbon paper while stirring, drying and curing after spraying to form a microporous layer, and obtaining a gas diffusion layer; The organic solvent in step S3 is selected from one or more of N-methylpyrrolidone, N-alkylpyrrolidone, and N,N-dimethylformamide.

[0008] By adopting the above technical scheme, in the spray slurry of the present application, N-methylpyrrolidone, N-alkylpyrrolidone, and N,N-dimethylformamide are selected as solvents to first disperse the conductive powder, which has good dispersing ability for the conductive powder. In addition, N-methylpyrrolidone, N-alkylpyrrolidone, and N,N-dimethylformamide can be mixed with water as solvents. The conductive powder is mixed with the above organic solvent to form a conductive powder slurry B, and then mixed with a hydrophobic slurry A added with water and a hydrophobic agent. The dispersibility of the conductive powder can be improved, the agglomeration of the powder in the mixed slurry can be reduced, and the uniformity of the microporous layer can be improved; on the other hand, the present application adopts a stirring and spraying method to prepare the microporous layer, which can ensure that the conductive powder will not settle in the mixed slurry and maintain a good dispersion state. The prepared microporous layer is evenly dispersed, the surface roughness is smaller, the limiting current density of the gas diffusion layer battery is larger, the current stability is better, and the power density reaches 1.4W / cm -2 Moreover, compared with the current coating method, the spraying method used in this application can more accurately control the amount of slurry, improve the stability of product batches, and save the amount of slurry.

[0009] Optionally, the hydrophobic agent is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, fluorinated ethylene propylene, polydimethylsiloxane, and perfluorovinyl ether; The conductive powder is conductive carbon powder, and the conductive carbon powder is one or more selected from carbon black, acetylene black, activated carbon, graphite powder, carbon nanotubes, graphene oxide, and graphene; The surfactant is selected from one or more of dodecyltrimethylammonium bromide, Tween series, sodium dodecylbenzene sulfonate, and sodium lignin sulfate; The binder is selected from one or more of polyvinyl pyrrolidone, polyethylene glycol, hydroxyethyl cellulose and carboxymethyl cellulose.

[0010] By adopting the above-mentioned technical scheme, in this application, the hydrophobic properties of the microporous layer are regulated by adding a hydrophobic agent, and a gas diffusion layer with a contact angle of about 140° is obtained, which avoids water flooding and has a relatively high transmission efficiency for gas. In addition, a binder is added in this application. Compared with the currently commonly used microporous layer raw materials that are wet-coated on carbon paper, this application adopts a spraying method. The added binder can effectively adhere the mixed slurry containing conductive powder to the hydrophobic carbon paper during the spraying process, prevent it from falling off or flowing during spraying and subsequent processing, and improve the uniformity of the microporous layer and the quality of the diffusion layer.

[0011] Optionally, in step S3, the hydrophobic agent in the spray slurry C accounts for 3-15wt%, the conductive powder accounts for 3-13wt%, the surfactant accounts for 0.1-5wt%, the binder accounts for 0.2-10wt%, the organic solvent accounts for 25-35wt%, and the balance is water.

[0012] By adopting the above technical solution, the comprehensive performance of the microporous layer obtained by spraying slurry C using the above ratio is better.

[0013] Optionally, the spraying in step S3 is high-pressure spraying, and the spraying pressure is 0.4-0.6 MPa.

[0014] By adopting the above technical solution, the mixed slurry is sprayed on the hydrophobic carbon paper by high pressure spraying in this application. During the spraying process, the sprayed slurry is atomized into tiny droplets by high pressure gas and sprayed evenly onto the surface of the carbon paper, ensuring the uniform distribution of the microporous layer on the carbon paper, which helps to improve the quality of the microporous layer and the quality of the gas diffusion layer. In addition, the high pressure spraying method in this application can accurately control the amount of mixed slurry, improve the stability of product batches and save the amount of slurry.

[0015] Optionally, after spraying in step S3, drying is first performed, and then hot pressing and curing and sintering are performed. The hot pressing temperature is 180-350° C. and the hot pressing pressure is 1-5 MPa.

[0016] By adopting the above-mentioned technical scheme, a hot pressing process is adopted in the present application, and under external pressure conditions, the slurry in the microporous layer is pressed more into the pore structure of the carbon paper layer, thereby improving the bonding force between the microporous layer and the carbon paper layer, reducing the separation phenomenon between the microporous layer and the carbon paper layer, improving the quality of the gas diffusion layer, and controlling the product thickness. When the slurry is evenly dispersed, the consistency of the product can be improved.

[0017] Optionally, in step S3, the curing and sintering temperature is 300-380° C., and the curing and sintering is performed at normal pressure for 0.5-1.5 h.

[0018] Optionally, the specific operation of curing and sintering in step S3 is: First, heat to 180-200°C, cure at normal pressure for 15-20 minutes, then heat to 280-300°C, evacuate to -0.8-(-0.1)MPa under this temperature condition, treat for 20-30 minutes, then treat at normal pressure and 220-240°C for 10-20 minutes, then heat to 300-380°C, and cure at normal pressure for 0.5-1.5h.

[0019] By adopting the above technical scheme, a segmented curing method is adopted after spraying is completed. First, preliminary curing is carried out at low temperature, and then the temperature is increased and treated under negative pressure conditions. Under vacuum adsorption conditions, the microporous layer is made to fit more tightly on the hydrophobic carbon paper. Then the temperature is reduced and treated at normal pressure. The above vacuum adsorption and post-fixing treatment is carried out to make the bonding between the microporous layer and the carbon paper more stable, and the internal stress caused by the heating and negative pressure treatment can be eliminated. Finally, a high-temperature curing treatment is carried out to form a stronger bond between the microporous layer and the carbon paper layer. In this way, the problem of poor bonding between the microporous layer and the carbon paper layer due to the shrinkage of the binder in the microporous layer after high-temperature sintering, and the separation of the microporous layer due to gaps can be alleviated, thereby improving the overall mechanical properties of the gas diffusion layer and ensuring its stability and durability in the fuel cell.

[0020] Optionally, during the curing and sintering treatment in step S3, the temperature is first raised to 180-200°C at a heating rate of 15-18°C / min, then raised to 280-300°C at a heating rate of 12-15°C / min, then cooled to 220-240°C with the furnace, and finally raised to 300-380°C at a heating rate of 5-10°C / min.

[0021] By adopting the above technical scheme, in the present application, the temperature is first increased at a faster heating rate, which, on the one hand, helps to volatilize the solvent in the spray slurry and avoids the voids or bubbles generated during the subsequent treatment that affect the bonding between the microporous layer and the carbon paper layer. Then, the temperature is increased at a faster heating rate but lower than that in the first stage, which helps to alleviate the impact of the curing shrinkage of the binder under high temperature conditions and improve the bonding strength between the microporous layer and the carbon paper layer. After vacuum treatment with the furnace cooling, the temperature is finally increased at a lower rate, which helps to completely cure the binder and evenly distribute the conductive powder under high temperature conditions. At the same time, the low heating rate alleviates the gap between the microporous layer and the carbon paper layer caused by rapid curing shrinkage at high temperature, which leads to the detachment of the microporous layer, thereby improving the quality and performance of the gas diffusion layer.

[0022] Optionally, the binder includes at least 20-30 wt % of versatate, and the remainder is one or more of polyvinyl pyrrolidone, polyethylene glycol, hydroxyethyl cellulose, and carboxymethyl cellulose.

[0023] By adopting the above technical scheme, it is found that when the binder is selected from the above-mentioned versatate vinyl ester and a binder such as polyethylene glycol, on the one hand, its hydrophilicity and hydrophobicity are balanced to achieve the adjustment of the hydrophobic properties on the microporous layer. On the other hand, it may be the interface effect of the compounding of versatate vinyl ester with other adhesives, or it may be the steric hindrance effect of the versatile carbonic acid group in versatate vinyl ester, which has higher thermal stability. It is found that when versatate vinyl ester is added to the binder and compounded with other binders, the problem of detachment of the microporous layer due to shrinkage of the binder can be alleviated, and a gas diffusion layer with better mechanical properties can be obtained.

[0024] Optionally, a silane coupling agent and nano silicon powder are further added to the conductive powder slurry B, wherein the amount of the silane coupling agent added is 0.5-1.5wt% of the amount of the conductive powder added, and the amount of the nano silicon powder added is 0.1-0.3wt% of the amount of the conductive powder added.

[0025] By adopting the above technical scheme, silane coupling agent and nano silicon powder are also added to the conductive powder slurry in the present application. The silane coupling agent serves as an interface improver, which makes it easier for the binder to adhere to the hydrophobic carbon paper, helps to reduce the pores and defects during the sintering process, improves the shrinkage phenomenon during the curing and sintering process of the binder, and can also enhance the interaction between the spray slurry and the carbon paper. The addition of nano silicon powder can form a chemical bond with the binder after being activated by the silane coupling agent, thereby improving the interface compatibility and thermal stability, helping to reduce the voids at the interface, and can fill the voids and defects after the shrinkage of the binder after curing and sintering, and can form a carbon-silicon chemical bond with the carbon paper, and can form silicon nitride with an organic solvent, which helps to fill the shrinkage voids, and ultimately improve the bonding strength between the microporous layer and the carbon paper layer, and improve the quality and performance of the gas diffusion layer.

[0026] Optionally, the specific operation of step S2 is: immersing the porous base layer carbon paper in step S1 in a polytetrafluoroethylene hydrophobic liquid for 1-20 minutes, and then drying and hot pressing the paper, the hot pressing temperature is 180-350°C, the hot pressing pressure is 1-5MPa, and then curing and sintering the paper at 300-380°C for 30-150 minutes to obtain hydrophobic carbon paper.

[0027] In a second aspect, the present application provides a gas diffusion layer, which adopts the following technical solution: A gas diffusion layer is prepared by the preparation method.

[0028] By adopting the above technical solution, the gas diffusion layer obtained by the method provided by the present application has a certain degree of hydrophobicity regulation, the hydrophobic contact angle reaches 145°, and the power density of the gas diffusion layer reaches 1.4W / cm -2 , and the surface roughness of the gas diffusion layer is low, the microporous layer and the carbon paper substrate layer have good bonding, and the proton exchange fuel cell loaded with it has better current stability and greater limiting current density.

[0029] In a third aspect, the present application provides a proton exchange membrane fuel cell, which adopts the following technical solution: A proton exchange membrane fuel cell comprises the gas diffusion layer.

[0030] In summary, this application has the following beneficial effects: 1. In the present application, N-methylpyrrolidone, N-alkylpyrrolidone, and N,N-dimethylformamide are selected as solvents in the spray slurry to first disperse the conductive powder. The solvents have good dispersibility for the conductive powder. In addition, N-methylpyrrolidone, N-alkylpyrrolidone, and N,N-dimethylformamide can be mixed with water at will as solvents. The conductive powder is mixed with the above organic solvent to form a conductive powder slurry B, which is then mixed with a hydrophobic slurry A to which water and a hydrophobic agent are added. This can improve the dispersibility of the conductive powder, reduce the agglomeration of the powder in the mixed slurry, and improve the uniformity of the microporous layer; 2. In this application, the microporous layer is prepared by stirring and spraying, which can ensure that the conductive powder will not settle in the mixed slurry and maintain a good dispersion state. The prepared microporous layer is evenly dispersed, with a smaller surface roughness. The limiting current density of the gas diffusion layer battery is larger, the current stability is better, and the power density reaches 1.4W / cm -2 ; 3. In the present application, a hot pressing process is adopted, and under external pressure conditions, the slurry in the microporous layer is pressed more into the pore structure of the carbon paper layer, thereby improving the bonding force between the microporous layer and the carbon paper layer, reducing the separation phenomenon between the microporous layer and the carbon paper layer, improving the quality of the gas diffusion layer, and controlling the product thickness. When the slurry is evenly dispersed, the consistency of the product can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a hydrophobic effect diagram of the gas diffusion layer prepared in Example 1 of the present application, and its hydrophobic angle is 145°; Figure 2 This is the electrochemical performance diagram of the gas diffusion layer obtained in Example 1 of the present application, and the power density of the gas diffusion layer is 1.4W / cm -2 . DETAILED DESCRIPTION

[0032] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0033] The porous base layer carbon paper in step S1 in the following examples is the carbon paper obtained according to the method in Example 1 in the application publication number CN118610483A.

[0034] The polytetrafluoroethylene emulsion in the following embodiments is polytetrafluoroethylene emulsion model DISP 30 produced by Dongguan Zhanyang Polymer Materials Co., Ltd.

[0035] The high-pressure spraying in step S3 of the following embodiment is spraying while stirring, which can be achieved by a currently commercially available stirring and spraying integrated machine, or a stirring head is provided in the spraying slurry tank, and an external motor is used to spray the mixed slurry in the slurry tank in a mixed state.

[0036] Example 1 A method for preparing a gas diffusion layer comprises the following steps: S1, preparing a porous base layer of carbon paper; S2, the porous substrate carbon paper in step S1 is immersed in a polytetrafluoroethylene hydrophobic liquid for 10 minutes, and then dried at 80°C for 40 minutes and then hot pressed at a temperature of 280°C and a pressure of 3MPa, and then cured and sintered at 350°C for 120 minutes to obtain a PTFE (polytetrafluoroethylene) hydrophobic carbon paper with a PTFE (polytetrafluoroethylene) loading of 15wt%, wherein the hydrophobic liquid is obtained by mixing a polytetrafluoroethylene emulsion and water, the hydrophobic liquid is obtained by mixing a polytetrafluoroethylene emulsion with a solid content of 60% and water, and the mass concentration of polytetrafluoroethylene in the hydrophobic liquid is 10wt%; S3, mixing a hydrophobic agent (specifically a polytetrafluoroethylene emulsion with a solid content of 60%) with water to obtain a hydrophobic slurry A, such that the mass concentration of polytetrafluoroethylene in the hydrophobic slurry A is 10%; Conductive powder, surfactant, binder and organic solvent are stirred and ultrasonically mixed and dispersed to obtain conductive powder slurry B, so that the solid mass concentration (the sum of the mass of conductive powder, surfactant and binder) in conductive powder slurry B is 10wt%, and the balance is organic solvent; The hydrophobic slurry A and the conductive powder slurry B are mixed to form a spray slurry C, so that the hydrophobic agent polytetrafluoroethylene accounts for 10wt%, the conductive powder accounts for 10wt%, the surfactant accounts for 2wt%, the binder accounts for 5wt%, the organic solvent accounts for 30wt%, and the balance is water in the slurry C; Then the spray slurry C was sprayed on the hydrophobic carbon paper while stirring, and the spraying was high-pressure spraying, the spraying pressure was 0.5MPa, and then dried at 80°C, and then hot pressed, the hot pressing temperature was 280°C, the hot pressing pressure was 3MPa, and after the hot pressing treatment, it was cured and sintered at normal pressure to form a microporous layer, the curing and sintering temperature was 350°C, and the curing and sintering was performed for 1h to obtain a gas diffusion layer with a microporous layer as the upper layer and a carbon paper pore base layer as the lower layer, and the gas diffusion layer microporous layer loading was 1.2mg / cm 2 ; Among them, in step S3, the conductive powder is conductive carbon powder, and the conductive carbon powder is carbon black; the surfactant is sodium dodecylbenzene sulfonate; the binder is polyvinyl pyrrolidone; and the organic solvent is N-methylpyrrolidone.

[0037] In this embodiment, the hot pressing treatments in steps S2 and S3 are both performed by an isostatic double steel belt press.

[0038] The surface roughness of the microporous layer of the gas diffusion layer obtained in Example 1 was tested, and its surface roughness was 0.22 μm, which was less than 0.8 μm, and the surface roughness was low. In addition, the contact angle of the hydrophobic gas diffusion layer obtained in this example was as follows: Figure 1 As shown, the hydrophobic angle reaches 145°.

[0039] Example 2 A method for preparing a gas diffusion layer comprises the following steps: S1, preparing a porous base layer of carbon paper; S2, the porous substrate carbon paper in step S1 is immersed in a polytetrafluoroethylene hydrophobic liquid for 1 min, and then dried at 60°C for 90 min and then hot pressed at a temperature of 180°C and a pressure of 5 MPa, and then cured and sintered at 300°C for 150 min to obtain a PTFE (polytetrafluoroethylene) hydrophobic carbon paper with a PTFE (polytetrafluoroethylene) loading of 5 wt%, wherein the hydrophobic liquid is obtained by mixing a polytetrafluoroethylene emulsion with a solid content of 60% with water, and the mass concentration of polytetrafluoroethylene in the hydrophobic liquid is 20 wt%; S3, mixing the hydrophobic agent polyvinylidene fluoride emulsion with water to obtain a hydrophobic slurry A, so that the mass concentration of the polyvinylidene fluoride in the hydrophobic slurry A is 7%; Conductive powder, surfactant, binder and organic solvent are stirred and ultrasonically mixed and dispersed to obtain conductive powder slurry B, so that the solid mass concentration (the sum of the mass of conductive powder, surfactant and binder) in conductive powder slurry B is 5wt%, and the balance is organic solvent; The hydrophobic slurry A and the conductive powder slurry B are mixed to form a spray slurry C, so that the hydrophobic agent polyvinylidene fluoride accounts for 3wt%, the conductive powder accounts for 3wt%, the surfactant accounts for 0.1wt%, the binder accounts for 0.2wt%, the organic solvent accounts for 25wt%, and the balance is water; Then the spray slurry C was sprayed on the hydrophobic carbon paper while stirring, and the spraying was high-pressure spraying, the spraying pressure was 0.4MPa, and then dried at 60°C, and then hot pressed at a temperature of 180°C and a pressure of 5MPa. After the hot pressed treatment, it was cured and sintered at normal pressure to form a microporous layer, the curing and sintering temperature was 300°C, and the curing and sintering was performed for 1.5h to obtain a gas diffusion layer with a microporous layer as the upper layer and a carbon paper pore base layer as the lower layer, and the gas diffusion layer microporous layer loading was 0.8mg / cm 2 ; Among them, in step S3, the conductive powder is conductive carbon powder, conductive carbon powder graphite powder; the surfactant is Tween 80; the binder is hydroxyethyl cellulose; and the organic solvent is N-alkyl pyrrolidone.

[0040] In this embodiment, the hot pressing treatments in steps S2 and S3 are both performed by an isostatic double steel belt press.

[0041] The surface roughness of the microporous layer of the gas diffusion layer obtained in Example 1 was tested, and the surface roughness was 0.26 um, which was less than 0.8 um, and the surface roughness was low.

[0042] Example 3 A method for preparing a gas diffusion layer comprises the following steps: S1, preparing a porous base layer of carbon paper; S2, the porous substrate carbon paper in step S1 is immersed in a polytetrafluoroethylene hydrophobic liquid for 20 minutes, and then dried at 100°C for 20 minutes and then hot-pressed, the hot-pressing temperature is 350°C, the hot-pressing pressure is 1MPa, and then cured and sintered at 380°C for 30 minutes to obtain a PTFE (polytetrafluoroethylene) hydrophobic carbon paper with a PTFE (polytetrafluoroethylene) loading of 25wt%, wherein the hydrophobic liquid is obtained by mixing a polytetrafluoroethylene emulsion and water, the hydrophobic liquid is obtained by mixing a polytetrafluoroethylene emulsion with a solid content of 60wt% and water, and the mass concentration of polytetrafluoroethylene in the hydrophobic liquid is 5wt%; S3, mixing the hydrophobic agent polydimethylsiloxane emulsion with water to obtain a hydrophobic slurry A, so that the mass concentration of polydimethylsiloxane in the hydrophobic slurry A is 30%; Conductive powder, surfactant, binder and organic solvent are stirred and ultrasonically mixed and dispersed to obtain conductive powder slurry B, so that the solid mass concentration (the sum of the mass of conductive powder, surfactant and binder) in conductive powder slurry B is 20wt%, and the balance is organic solvent; The hydrophobic slurry A and the conductive powder slurry B are mixed to form a spray slurry C, so that the hydrophobic agent polydimethylsiloxane accounts for 15wt%, the conductive powder accounts for 13wt%, the surfactant accounts for 5wt%, the binder accounts for 10wt%, the organic solvent accounts for 35wt%, and the balance is water in the slurry C; Then the spray slurry C was sprayed on the hydrophobic carbon paper while stirring, and the spraying was high-pressure spraying, the spraying pressure was 0.6MPa, and then dried at 100°C, and then hot pressed, the hot pressing temperature was 350°C, the hot pressing pressure was 5MPa, and after the hot pressing treatment, it was cured and sintered at normal pressure to form a microporous layer, the curing and sintering temperature was 380°C, and the curing and sintering was performed for 0.5h to obtain a gas diffusion layer with a microporous layer as the upper layer and a carbon paper pore base layer as the lower layer, and the gas diffusion layer microporous layer loading was 2mg / cm 2 ; Among them, the conductive powder is conductive carbon powder, and the conductive carbon powder is graphene; the surfactant is dodecyltrimethylammonium bromide; the binder is polyethylene glycol; and the organic solvent is N,N-dimethylformamide.

[0043] In this embodiment, the hot pressing treatments in steps S2 and S3 are both performed by an isostatic double steel belt press.

[0044] The surface roughness of the microporous layer of the gas diffusion layer obtained in Example 1 was tested, and the surface roughness was 0.3 um, which was less than 0.8 um, and the surface roughness was low.

[0045] Example 4 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that the specific operation of curing and sintering is: first heating to 280°C at a heating rate of 10°C / min, keeping the temperature for 30 minutes, then heating to 350°C at a heating rate of 10°C / min, and curing and sintering for 1 hour.

[0046] Example 5 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that the specific operation of curing and sintering is: first, the temperature is increased to 190°C at a heating rate of 16°C / min, and the curing treatment is carried out at normal pressure for 15 minutes, then the temperature is increased to 290°C at a heating rate of 13°C / min, and under this temperature condition, the vacuum is evacuated to -0.5MPa (0.5MPa lower than atmospheric pressure) for 25 minutes, and then the furnace is cooled to 230°C and the treatment is carried out at normal pressure for 15 minutes, and finally the temperature is increased to 350°C at a heating rate of 10°C / min, and the curing treatment is carried out at normal pressure for 1 hour.

[0047] Example 6 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that the specific operation of curing and sintering is: first, the temperature is increased to 180°C at a heating rate of 15°C / min, and the curing treatment is carried out at normal pressure for 20 minutes, then the temperature is increased to 280°C at a heating rate of 12°C / min, and under this temperature condition, the vacuum is evacuated to -0.8MPa and the treatment is carried out for 30 minutes, then the furnace is cooled to 220°C and the treatment is carried out at normal pressure for 20 minutes, and finally the temperature is increased to 300°C at a heating rate of 5°C / min, and the curing treatment is carried out at normal pressure for 1.5 hours.

[0048] Example 7 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that the specific operation of curing and sintering is: first, the temperature is increased to 200°C at a heating rate of 18°C / min, and the curing treatment is carried out at normal pressure for 15 minutes, then the temperature is increased to 300°C at a heating rate of 15°C / min, and under this temperature condition, the vacuum is evacuated to -0.1MPa and the treatment is carried out for 20 minutes, then the furnace is cooled to 240°C and the treatment is carried out at normal pressure for 10 minutes, and finally the temperature is increased to 380°C at a heating rate of 10°C / min, and the curing treatment is carried out at normal pressure for 0.5 hours.

[0049] Example 8 A method for preparing a gas diffusion layer is carried out according to the method in Example 5, except that during the solidification and sintering, the temperature is directly raised to 350° C. without cooling after being treated in a vacuum state.

[0050] Example 9 A method for preparing a gas diffusion layer is carried out according to the method in Example 5, except that during the curing and sintering, the process is carried out at normal pressure without vacuuming during the treatment at 290°C.

[0051] Example 10 A method for preparing a gas diffusion layer is carried out according to the method in Example 5, except that the heating rate during the curing and sintering process is controlled to be 10° C. / min.

[0052] Embodiment 11 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that the binder in step S3 comprises a mixture of versatate and polyvinyl pyrrolidone in a mass ratio of 2.5:7.5.

[0053] Example 12 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that the binder in step S3 comprises a mixture of versatate and polyethylene glycol in a mass ratio of 2:8.

[0054] Example 13 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that the binder in step S3 comprises a mixture of versatate and hydroxyethyl cellulose in a mass ratio of 2:8.

[0055] Embodiment 14 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that a silane coupling agent and nano silicon powder are also added to the conductive powder slurry B in step S3, the amount of the silane coupling agent added is 1wt% of the conductive powder added, and the amount of the nano silicon powder added is 0.2wt% of the conductive powder.

[0056] Embodiment 15 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that a silane coupling agent and nano silicon powder are also added to the conductive powder slurry B in step S3, the amount of the silane coupling agent added is 0.5wt% of the conductive powder added, and the amount of the nano silicon powder added is 0.1wt% of the conductive powder.

[0057] Example 16 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that a silane coupling agent and nano silicon powder are also added to the conductive powder slurry B in step S3, the amount of the silane coupling agent added is 1.5wt% of the conductive powder added, and the amount of the nano silicon powder added is 0.3wt% of the conductive powder.

[0058] Embodiment 17 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that no hot pressing is performed in step S3, and the layer is directly dried, cured and sintered after spraying.

[0059] Comparative Example 1 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that the organic solvent in step S3 is replaced by water in an equal amount.

[0060] Comparative Example 2 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that ethanol is used as the organic solvent in step S3.

[0061] Comparative Example 3 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that 10wt% of a hydrophobic agent, 7wt% of a conductive powder, 2wt% of a surfactant, 4wt% of a binder and the remainder of water are directly mixed and dispersed to obtain a spray slurry C.

[0062] Comparative Example 4 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that the adhesive in step S3 is E-44 epoxy resin.

[0063] Comparative Example 5 A method for preparing a gas diffusion layer is carried out according to the method in Example 1, except that the method of spraying while stirring in step S3 is replaced by scraping.

[0064] Performance Testing The surface roughness of the microporous layer on the gas diffusion layer obtained in Examples 1-3, Examples 11-17 and the comparative examples of the present application was tested, and the test results are shown in Table 1 below. At the same time, the tensile strength of the gas diffusion layer obtained in the examples and the comparative examples was tested, and the test results are shown in Table 2 below.

[0065] Table 1: Referring to the test results in Table 1 above, the surface roughness of the microporous layer prepared in the embodiment of the present application is less than 0.8um, the microporous layer is evenly dispersed, and the surface roughness of the gas diffusion layer is smaller, which helps to improve the limiting current density and current stability of the battery. Figure 2 The gas diffusion layer prepared in Example 1 was assembled into a battery with electrochemical performance as shown in FIG. Figure 2 As shown, the power density of the gas diffusion layer reaches 1.4W / cm -2 .

[0066] Table 2: Table 2 continued: Performance Testing Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Tensile strength / MPa 24.6 25.3 22.1 26.7 25.9 Referring to the test results in Table 2 above, the gas diffusion layer prepared in the embodiment of the present application has better tensile strength, and the bonding between the microporous layer and the carbon paper layer is more solid. Referring to the test results of Example 1 and Example 4, compared with the sintering system in Example 2, Example 4 adopts a step-by-step treatment, while Example 1 adopts a fixed constant temperature treatment, and the tensile strength in Example 4 is improved. Combining the test results of Examples 5-7, when the step-by-step heating is adopted and the process is accompanied by vacuum adsorption treatment and temperature return cooling treatment, the tensile strength is significantly improved. Referring to the test results of Examples 8 and 9, when the process is not cooled or vacuumed, the tensile strength is reduced, and the bonding between the microporous layer and the carbon paper layer is weakened. Referring to the test results of Example 10, when the temperature is increased at a constant temperature heating rate during the curing and sintering process, the tensile strength is also reduced compared with Example 5, and the bonding between the microporous layer and the elastic finger layer is reduced. Referring to Example 10, when the temperature is increased at a constant temperature heating rate during the curing and sintering process, the tensile strength is also reduced compared with Example 5, and the bonding between the microporous layer and the elastic finger layer is reduced. According to the test results of Example 1 and Examples 11-13, when tert-butyl vinyl carbonate and traditional binders are used as binders, the tensile strength is improved compared with Example 1. This may be because tert-butyl vinyl carbonate has higher thermal stability, which can alleviate the problem of curing shrinkage of the binder and improve the bonding strength between the microporous layer and the carbon paper layer. Combined with the test results in Table 1, when tert-butyl vinyl carbonate is used, the compatibility of the slurry is better, and its surface roughness is equivalent to that of Example 1. Moreover, the hydrophobic angle of Example 11 is 147° after detection. Combined with the test results of Examples 14-16, when silane coupling agent and nano-silicon powder are also added to slurry B, its tensile strength is significantly improved. Combined with the test results of Example 17, when hot pressing treatment is not performed in step S3, its surface roughness and tensile strength are slightly reduced.

[0067] Combining the test results of Example 1 and Comparative Example 1, when traditional water or ethanol is used as the solvent in the raw material of the microporous layer, the dispersibility of the conductive carbon powder in the system is poor, and the surface roughness of the final microporous layer is significantly reduced, and its tensile strength is also significantly reduced. Referring to the test results in Example 3, when ordinary one-time direct mixing and dispersion is selected and water is selected as the common solvent, its surface roughness and tensile strength are significantly reduced. Combining the test results of Comparative Example 4, when epoxy resin is selected as the adhesive, its dispersibility may be relatively reduced in this application, and it may also be due to the relationship between the system and spraying, and its surface roughness is reduced. Combined with the test results in Comparative Example 5, when traditional scraping is selected, its surface roughness is low and the tensile strength is also low.

[0068] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a gas diffusion layer, characterized in that: The following steps are involved: S1, preparing a porous base layer of carbon paper; S2, performing hydrophobic treatment on the porous substrate carbon paper to obtain hydrophobic carbon paper; S3, mixing a hydrophobic agent with water to obtain a hydrophobic slurry A, mixing and dispersing a conductive powder, a surfactant, a binder and an organic solvent to obtain a conductive powder slurry B, mixing the hydrophobic slurry A with the conductive powder slurry B to form a spray slurry C, and then spraying the spray slurry C on a hydrophobic carbon paper while stirring, drying, curing and sintering after spraying to form a microporous layer, and obtaining a gas diffusion layer; The organic solvent in step S3 is selected from one or more of N-methylpyrrolidone, N-alkylpyrrolidone, and N,N-dimethylformamide.

2. The method for preparing a gas diffusion layer according to claim 1, characterized in that: The hydrophobic agent is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, fluorinated ethylene propylene, polydimethylsiloxane, and perfluorovinyl ether; The conductive powder is conductive carbon powder, and the conductive carbon powder is one or more selected from carbon black, acetylene black, activated carbon, graphite powder, carbon nanotubes, graphene oxide, and graphene; The surfactant is selected from one or more of dodecyltrimethylammonium bromide, Tween series, sodium dodecylbenzene sulfonate, and sodium lignin sulfate; The binder is selected from one or more of polyvinyl pyrrolidone, polyethylene glycol, hydroxyethyl cellulose and carboxymethyl cellulose.

3. The method for preparing a gas diffusion layer according to claim 1, characterized in that: In step S3, the spray slurry C contains 3-15wt% of hydrophobic agent, 3-13wt% of conductive powder, 0.1-5wt% of surfactant, 0.2-10wt% of binder, 25-35wt% of organic solvent, and the balance is water.

4. The method for preparing a gas diffusion layer according to claim 1, characterized in that: The spraying in step S3 is high-pressure spraying, and the spraying pressure is 0.4-0.6 MPa.

5. The method for preparing a gas diffusion layer according to claim 1, characterized in that: After spraying in step S3, drying is first performed, and then hot pressing and curing sintering are performed. The hot pressing temperature is 180-350° C. and the hot pressing pressure is 1-5 MPa.

6. The method for preparing a gas diffusion layer according to claim 1, characterized in that: In step S3, the curing and sintering temperature is 300-380° C., and the curing and sintering is carried out at normal pressure for 0.5-1.5 h.

7. The method for preparing a gas diffusion layer according to claim 1, characterized in that: The specific operation of curing and sintering in step S3 is as follows: First, heat to 180-200°C, cure at normal pressure for 15-20 minutes, then heat to 280-300°C, evacuate to -0.8-(-0.1)MPa under this temperature condition, treat for 20-30 minutes, then heat to 300-380°C at normal pressure and 220-240°C for 10-20 minutes, and cure at normal pressure for 0.5-1.5 hours.

8. The method for preparing a gas diffusion layer according to claim 1, characterized in that: The specific operation of step S2 is: immersing the porous base layer carbon paper in step S1 in a polytetrafluoroethylene hydrophobic liquid for 1-20 minutes, then drying and hot pressing, the hot pressing temperature is 180-350°C, the hot pressing pressure is 1-5MPa, and then curing and sintering at a temperature of 300-380°C for 30-150 minutes to obtain hydrophobic carbon paper.

9. A gas diffusion layer obtained by the method according to any one of claims 1 to 8.

10. A proton exchange membrane fuel cell, characterized in that: Comprising a gas diffusion layer as claimed in claim 9.

Citation Information

Patent Citations

  • Fuel cell gas diffusion layer, preparation method thereof and fuel cell

    CN114464834A

  • Preparation method of gas diffusion layer for fuel cell

    CN114927704A

  • High-performance carbon paper and preparation method thereof

    CN118610483A

Cited By

  • Thermally stable gas diffusion layer material and fuel cell

    CN120497357A

  • Gas diffusion layer for fuel cell as well as preparation method and application of gas diffusion layer

    CN121172173A